Adaptive Leadership as Leadership Strategy on Curriculum Change: a Case Study in XYZ School - Budi Wibawanta; Ester Abigail Tanio (EduInovasi: Journal of Basic Educational Studies, 2024)
As curriculum change is inevitable in education, the principal plays an important role in the process of curriculum change. The importance of the right leadership strategy in implementing curriculum changes in a school is very crucial. Adaptive leadership is one of leadership strategy that can be applied by principal as the school hinders with curriculum change. This study is qualitative research with the case study method in XYZ School, in which the principal applied the adaptive leadership as his strategy on curriculum change. The results showed that the implementation of adaptive leadership at XYZ School has supported the process of curriculum change. The principals are able to support the teachers on their role as change implementer, feedback giver and collaborator.